l-Tyrosine immobilized on multiwalled carbon nanotubes: A new substrate for thallium separation and speciation using stabilized temperature platform furnace-electrothermal atomic absorption spectrometry - Pacheco, Pablo Hugo (2009)
An approach for the separation and determination of inorganic thallium species is described. A new sorbent, l-tyrosine-carbon nanotubes (l-tyr-CNTs), was used and applied to the analysis of tap water samples. At pH 5.0, l-tyr was selective only towards Tl(III), while total thallium was determined directly by stabilized temperature platform furnace-electrothermal atomic absorption spectrometry (STPF-ETAAS). The Tl(III) specie, which was retained by l-tyrosine, was quantitatively eluted from the column with 10% of nitric acid. An on-line breakthrough curve was used to determine the column capacity, which resulted to be 9.00 μmol of Tl(III) g-1 of l-tyr-CNTs with a molar ratio of 0.14 (moles of Tl bound to moles of l-tyr at pH 5). Transient peak areas revealed that Tl stripping from the column occurred instantaneously. Effects of sample flow rate, concentration and flow rate of the eluent, and interfering ions on the recovery of the analyte were systematically investigated. The detection limit for the determination of total thallium (3σ) by STPF-ETAAS was 150 ng L-1. The detection limit (3σ) for Tl(III) employing the separation system was 3 ng L-1, with an enrichment factor of 40. The precision of the method expressed as the relative standard deviation (RSD) resulted to be 3.4%. The proposed method was applied to the speciation and determination of inorganic thallium in tap water samples. The found concentrations were in the range of 0.88-0.91 μg L-1 of Tl(III), and 3.69-3.91 μg L-1 of total thallium.